Peningkatan Kualitas Hidup Lansia melalui Pemeriksaan Tekanan Darah, Glukosa Darah dan Edukasi Menggunakan Media Informasi - Ayu Endang Purwati; Sri Utami Asmarani; Sri Wulan Ratna Dewi; Nur Hidayat (Yayasan Inspirasi El Burhani, 2023)
Introduction: One of the indicators of the success of national development in terms of health is the increasing life expectancy of the population. The increasing life expectancy of the Indonesian population has implications for the increasing number of elderly people. The elderly are a human age group that has entered the final stage of its life phase. The elderly group will experience a process called the aging process or often referred to as the aging process. One of the efforts to improve the quality of life of the elderly is to conduct regular health checks to monitor the emergence of degenerative diseases. Objective: The elderly community of Antralina hamlet brought to the madrasah as many as 26 people. Method: The method of implementation is by providing health counseling, checking blood pressure and blood glucose. Result: This community service is carried out to provide services for checking blood pressure, blood glucose and health counseling for the elderly by using information media. Conclusion: Availability of information media in the form of digital pocket books.